Catalyst system for ethylene polymerization
By using specific components and introduction methods in the catalyst system, the particle size distribution of catalyst particles is controlled, and the problems of uneven morphology and poor fluidity of polymer particles are solved, and efficient polyethylene production is achieved.
Patent Information
- Application Number
- CN202380088349.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-05
- Publication Date
- 2025-08-01
AI Technical Summary
During the polymerization process, the existing polyethylene catalyst system has problems such as uneven polymer particles, poor fluidity, many fine particles formation and low stacking density, resulting in unstable equipment operation and frequent cleaning, affecting production efficiency.
Using a catalyst system containing an organic magnesium oxygen-containing compound, an organic titanium oxygen-containing compound and an aluminum organohalide of a specific molar ratio, the average particle size distribution of the catalyst particles is controlled to be between 0.8 and 1.6 by simultaneously introducing a hydrocarbon solution and an aluminum organohalide in the reactor, thereby forming a polymer powder with good fluidity and uniform particle size.
The high bulk density, uniform particle size and good fluidity of the polymer powder are achieved, which reduces fine particle formation, improves production efficiency and simplifies the catalyst preparation process.
Smart Images

Figure CN120418306A_ABST
Abstract
Description
[0001] The present invention relates to a catalyst system for producing polyethylene and a method for producing polyethylene using the catalyst system.
[0002] Polyethylene can be produced in a gas phase, solution or slurry process. In an ethylene slurry polymerization process, a diluent such as hexane or isobutane is used to dissolve ethylene monomers, comonomers and hydrogen to polymerize the monomers in the presence of a catalyst system. After polymerization, the formed polyethylene product exists as a slurry of solid polyethylene particles suspended in a liquid medium, since the polyethylene polymer particles are insoluble or substantially insoluble in the diluent.
[0003] In a polyethylene polymerization process, good polymer particle morphology is required to enable smooth operation of the equipment. The polymer powder morphology includes, for example, the uniformity of polymer particle size and shape, good flowability and high bulk density.
[0004] The bulk density of a polymer powder refers to the mass of the powder per unit volume. This is an important parameter since the obtained powder has to be stored and transported.
[0005] A higher bulk density can, for example, reduce its blockage during transportation and can increase the storage amount per unit volume. By increasing the bulk density, the weight of polyethylene per unit volume present in the polymerization vessel will increase, and the concentration of polyethylene powder in the polymerization vessel will be increased.
[0006] In addition, the formation of small polymer particles (polymer particles < 100 μm) (also referred to as fines, which may be caused by the fragmentation of polymer particles) needs to be overcome. Specifically, the performance of dryers and decanters is affected by sheeting and fouling caused by small polymer particles. This fouling results in, for example, a reduction in the efficiency of heat exchangers. In addition, the apparatus needs to be cleaned more frequently, which is expensive and results in a loss of productivity. Also, the particles can deposit on sensors, which causes problems in controlling the polymerization process, or the deposition can cause blockages in pipelines.
[0007] At the same time, it is now widely recognized that the morphology of polymer particles mainly depends on the morphology of catalyst particles through a replication phenomenon. Therefore, it is necessary to improve the morphology of catalyst particles. At the same time, it is desirable for the catalyst to exhibit high activity. In addition to this, it is also required that the catalyst system can be synthesized on a commercial scale in an easy and simple manner.
[0008] Therefore, the object of the present invention is to provide a catalyst system which exhibits high catalyst activity, is easy to prepare and produces polyethylene powder particles which exhibit high powder bulk density, particle size uniformity, suitable morphology and good flowability.
[0009] It has surprisingly been found that this object is achieved at least in part by a catalyst system for producing polyethylene according to the present invention, which catalyst system comprises:
[0010] I) A reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0011] a) A hydrocarbon solution comprising:
[0012] i) A magnesium compound selected from organo-oxygen-containing magnesium compounds and / or halogen-containing magnesium compounds; and
[0013] ii) An organo-oxygen-containing titanium compound,
[0014] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0015] and
[0016] b) An organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0017] wherein the molar ratio of the organoaluminum halide I)b) supplied in the preparation of I) to the titanium supplied in I)a) is 1 - 12; and
[0018] wherein the average particle size distribution (PSD) of the catalyst particles is 0.8 - 1.6, and wherein PSD is defined as PSD = (D 90 - D 10 ) / D 50 , and D 10 , D 90 and D 50 are measured by laser diffraction as described in the specification, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0019] Preferably, a catalyst system for producing polyethylene according to the present invention, which catalyst system comprises:
[0020] I) A reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0021] a) A hydrocarbon solution comprising:
[0022] i) A magnesium compound selected from organo-oxygen-containing magnesium compounds and / or halogen-containing magnesium compounds; and
[0023] ii) An organo-oxygen-containing titanium compound,
[0024] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0025] and
[0026] b) an organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety having 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0027] wherein the molar ratio of the organoaluminum halide I)b) supplied in the preparation of I) to the titanium supplied in I)a) is 1 - 12; and
[0028] wherein the average particle size distribution (PSD) of the catalyst particles is 0.8 - 1.6, and wherein PSD is defined as PSD = (D 90 - D 10 ) / D 50 , and D 10 , D 90 and D 50 are measured by laser diffraction as described in the specification, wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0029] The average particle size distribution (PSD) can be defined as PSD = (D 90 - D 10 ) / D 50 , wherein D 90 is the percentile value representing the size below which 90% of all the particles are found, D 10 is the percentile value representing the size below which 10% of all the particles are found, D 50 is the percentile value representing the size below which 50% of all the particles are found, and wherein the particle size is determined using laser diffraction.
[0030] In one aspect of the present invention, the present invention relates to a catalyst system for producing polyethylene, which catalyst system is obtained or can be obtained by a method comprising the following steps:
[0031] a) providing a hydrocarbon solution comprising:
[0032] i) a magnesium compound selected from organooxygen-containing magnesium compounds; and / or halogen-containing magnesium compounds; and
[0033] ii) an organooxygen-containing titanium compound I)a);
[0034] wherein the molar ratio of magnesium:titanium is less than 3:1;
[0035] b) providing an organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety having 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0036] c) introducing the hydrocarbon solution and the organoaluminum halide into the reactor vessel simultaneously; and
[0037] d) obtaining a catalyst system comprising a reaction product (I) obtained by reacting the hydrocarbon solution with the organoaluminum halide;
[0038] wherein the molar ratio of the organoaluminum halide supplied in the preparation of (I) b) to the titanium supplied a) is 1 - 12; and
[0039] wherein the average particle size distribution (PSD) of the catalyst particles contained in the catalyst system is 0.8 - 1.6, and wherein PSD is defined as PSD = (D 90 - D 10 ) / D 50 , and D 10 , D 90 and D 50 are measured by laser diffraction as described in this specification.
[0040] The catalyst system according to the invention gives polymer powder particles that exhibit good flowability. This ensures that the powder can be easily metered into, for example, an extruder for pelletization. In addition, the polymer powder particles exhibit fewer fines and a uniform particle size distribution. Moreover, the catalyst system shows high productivity. This means that the catalyst residues in the polymer are very low.
[0041] A suitable way to improve flowability and reduce fines is by reducing the average particle size distribution of the catalyst system, which in turn reduces the average particle size distribution of the polymer powder formed.
[0042] Another advantage of the catalyst system is that the synthesis to produce the catalyst system is relatively simple and inexpensive and is based on compounds that are readily available and relatively easy to handle.
[0043] Furthermore, the inventors have surprisingly found that when the hydrocarbon solution and the organoaluminum halide I) b) are introduced into the reactor simultaneously rather than sequentially, the resulting catalyst system contains catalyst particles having the desired particle size span or average particle size distribution (PSD). Thus, the morphology and size of the catalyst particles contained in the catalyst system appear to be influenced by the way the catalyst system is prepared.
[0044] Thus, when such a catalyst system is used in the production of polyethylene, the resulting polyethylene has good powder morphology and flowability.
[0045] The expression "introducing the hydrocarbon solution and the organoaluminum halide into the reactor simultaneously" means that once the two components are separately prepared, they are directly combined while being introduced into the reactor.
[0046] Preferably, the catalyst system comprises:
[0047] I) Reaction products obtained by reacting the following components, preferably in a reactor vessel:
[0048] a) A hydrocarbon solution comprising:
[0049] i) A magnesium compound selected from organo-oxygenated magnesium compounds and / or halogen-containing magnesium compounds; and
[0050] ii) An organo-oxygenated titanium compound,
[0051] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0052] and
[0053] b) An organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0054] wherein the molar ratio of the organoaluminum halide I)b) supplied in the preparation of I) to the titanium supplied in I)a) is 1 - 12; and
[0055] wherein the average particle size distribution of the catalyst particles is 0.8 - 1.5, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0056] Preferably, the average particle diameter D 50 of the catalyst particles of the catalyst system is 3.5 - 12.50 μm, preferably 4.50 - 10 μm, more preferably 4.50 - 8 μm.
[0057] Preferably, the catalyst system comprises:
[0058] I) Reaction products obtained by reacting the following components, preferably in a reactor vessel:
[0059] a) A hydrocarbon solution comprising:
[0060] i) A magnesium compound selected from organo-oxygenated magnesium compounds and / or halogen-containing magnesium compounds; and
[0061] ii) An organo-oxygenated titanium compound,
[0062] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0063] and
[0064] b) An organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0065] wherein the molar ratio of the organoaluminum halide supplied in the preparation of I) b) to the titanium supplied in I) a) is 1-12; and
[0066] wherein the average particle size distribution of the catalyst particles is 0.8-1.5, and
[0067] wherein the average particle diameter D of the catalyst particles of the catalyst system 50 is 3.5-12.50 μm, preferably 3.50-10 μm, more preferably 4.50-8 μm, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0068] Preferably, the catalyst system comprises:
[0069] I) a reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0070] a) a hydrocarbon solution comprising:
[0071] i) a magnesium-containing compound selected from organo-oxygenated magnesium compounds and / or halogen-containing magnesium compounds; and
[0072] ii) an organo-oxygenated titanium compound,
[0073] wherein the molar ratio of magnesium:titanium is less than 3:1;
[0074] and
[0075] b) an organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety containing 1-10 carbon atoms, X is a halogen, and 0 < n < 3;
[0076] wherein the molar ratio of the organoaluminum halide I) b) supplied in the preparation of I) to the titanium supplied in I) a) is 4-12, preferably 5-10, more preferably 5-9, most preferably 6-9; and
[0077] wherein the average particle size distribution of the catalyst particles is 0.8-1.6, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0078] Preferably, the catalyst system comprises:
[0079] I) a reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0080] a) a hydrocarbon solution comprising:
[0081] i) a magnesium-containing compound selected from organo-oxygenated magnesium compounds and / or halogen-containing magnesium compounds; and
[0082] ii) an organo-oxygen-containing titanium compound,
[0083] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0084] and
[0085] b) an organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety having 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0086] wherein the molar ratio of the organoaluminum halide supplied in the preparation of I) b) to the titanium supplied in I) a) is 4 - 12, preferably 5 - 10, more preferably 5 - 9, most preferably 6 - 9, and wherein the average particle size distribution of the catalyst particles is 0.8 - 1.5, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0087] The organo-oxygen-containing magnesium compound can be selected, for example, from alkoxymagnesiums such as methoxymagnesium, ethoxymagnesium, and isopropoxymagnesium, alkylalkoxymagnesiums such as ethyl ethoxymagnesium, and carbalkoxymagnesiums such as ethyl carbonatemagnesium.
[0088] For example, the organo-oxygen-containing magnesium compound can be an alkoxymagnesium. For example, the alkoxymagnesium can be ethoxymagnesium (Mg(OC2H5)2).
[0089] The halogen-containing magnesium compound can be selected, for example, from magnesium dihalides and magnesium dihalide complexes. For example, the halide in the magnesium dihalide and magnesium dihalide complex can be chlorine.
[0090] The molar ratio of magnesium to titanium is less than 3:1. Preferably, the molar ratio of magnesium to titanium is 1.5:1 to 3:1.
[0091] Preferably, the catalyst system comprises:
[0092] I) a reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0093] a) a hydrocarbon solution comprising:
[0094] i) a magnesium-containing compound selected from organo-oxygen-containing magnesium compounds, preferably ethoxymagnesium (Mg(OC2H5)2); and
[0095] ii) an organo-oxygen-containing titanium compound,
[0096] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0097] and
[0098] b) an organoaluminum halide of the formula AlR n X 3-nOrganic aluminum halide, where R is a hydrocarbon structural moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0099] where the molar ratio of the organic aluminum halide supplied in the preparation of I) b) to the titanium supplied in I) a) is 1 - 12; and
[0100] where the average particle size distribution of the catalyst particles is 0.8 - 1.6, preferably where the hydrocarbon solution and the organic aluminum halide are supplied to the reactor vessel simultaneously.
[0101] The organic oxygen-containing titanium compound can be represented, for example, by the formula [TiO x (OR) 4-2x n where R represents an organic group, and 0 ≤ x ≤ 1 and 1 ≤ n ≤ 6.
[0102] Preferably, the catalyst system comprises:
[0103] I) The reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0104] a) A hydrocarbon solution comprising:
[0105] i) A magnesium-containing compound selected from organic oxygen-containing magnesium compounds and / or magnesium halides; and
[0106] ii) An organic oxygen-containing titanium compound represented by the formula [TiO x (OR) 4-2x n where
[0107] · R represents an organic group
[0108] · 0 ≤ x ≤ 1
[0109] · 1 ≤ n ≤ 6
[0110] where the molar ratio of magnesium:titanium is less than 3:1;
[0111] and
[0112] b) An organic aluminum halide of the formula AlR n X 3-n where R is a hydrocarbon structural moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0113] where the molar ratio of the organic aluminum halide supplied in the preparation of I) b) to the titanium supplied in I) a) is 1 - 12; and
[0114] where the average particle size distribution of the catalyst particles is 0.8 - 1.5, preferably where the hydrocarbon solution and the organic aluminum halide are supplied to the reactor vessel simultaneously.
[0115] Organic oxygen-containing titanium compounds can be selected, for example, from titanium alkoxides, titanium phenoxides, oxytitanium alkoxides, condensed titanium alkoxides, titanium carboxylates, and enolized titanium compounds.
[0116] Preferably, the oxygen-containing titanium compound is selected from titanium alkoxides. Titanium alkoxides can be selected, for example, from Ti(OC2H5)4, Ti(OC3H7)4, Ti(OC4H9)4, and Ti(OC8H 17 )4. Preferably, the titanium alkoxide is Ti(On-C4H9)4.
[0117] Preferably, the catalyst system comprises:
[0118] I) A reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0119] a) A hydrocarbon solution comprising:
[0120] i) A magnesium-containing compound selected from organic oxygen-containing magnesium compounds, which is magnesium ethoxide (Mg(OC2H5)2); and
[0121] ii) An organic oxygen-containing titanium compound of Ti(On-C4H9)4,
[0122] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0123] and
[0124] b) An organoaluminum halide of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3;
[0125] wherein the molar ratio of the organoaluminum halide I)b) supplied in the preparation of I) to the titanium supplied in I)a) is 1 - 12; and
[0126] wherein the average particle size distribution of the catalyst particles is 0.8 - 1.6, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0127] The organoaluminum halide I)b) can be, for example, a compound of the formula AlR n X 3-n wherein R is a hydrocarbon structural moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3; preferably 1.5 < n < 3.
[0128] The organoaluminum halide I)b) can be selected, for example, from aluminum ethyl dibromide, aluminum ethyl dichloride, aluminum propyl dichloride, aluminum n-butyl dichloride, aluminum isobutyl dichloride, diethylaluminum chloride, and diisobutylaluminum chloride. Preferably, X is chlorine. Preferably, the organoaluminum halide I)b) is an organoaluminum chloride. Most preferably, the organoaluminum halide I)b) is aluminum ethyl dichloride.
[0129] Preferably, the catalyst system comprises:
[0130] I) The reaction product obtained by reacting the following components, preferably in a reactor vessel:
[0131] a) A hydrocarbon solution comprising:
[0132] i) A magnesium-containing compound selected from organooxygenated magnesium compounds, which is magnesium ethoxide (Mg(OC2H5)2); and
[0133] ii) An organooxygenated titanium compound of Ti(On-C4H9)4,
[0134] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0135] and
[0136] b) The organoaluminum halide is aluminum ethyl dichloride;
[0137] wherein the molar ratio of the organoaluminum halide I)b) supplied in the preparation of I) to the titanium supplied in I)a) is 1 - 12; and
[0138] wherein the average particle size distribution of the catalyst particles is 0.8 - 1.6, preferably wherein the hydrocarbon solution and the organoaluminum halide are supplied to the reactor vessel simultaneously.
[0139] Preferably, the catalyst system for producing polyethylene is obtained or can be obtained by a method comprising the following steps:
[0140] a) Providing a hydrocarbon solution comprising:
[0141] i) A magnesium-containing compound selected from organooxygenated magnesium compounds; and
[0142] ii) The organooxygenated titanium compound I)a);
[0143] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0144] b) Providing an organoaluminum halide I)b) of the formula AlR n X 3-n wherein R is a hydrocarbon moiety containing 1 - 10 carbon atoms, 'X' is a halogen, and 0 < n < 3;
[0145] c) introducing a hydrocarbon solution and an organoaluminum halide into a reactor vessel simultaneously; and
[0146] d) obtaining a catalyst system comprising a reaction product (I) obtained by reacting the hydrocarbon solution with the organoaluminum halide;
[0147] · wherein the molar ratio of the organoaluminum halide I) b) supplied to the titanium I) a) supplied is 1 - 12; and
[0148] · wherein the average particle size distribution (PSD) of the catalyst particles contained in the catalyst system is 0.8 - 1.6, and wherein PSD is defined as PSD = (D 90 -D 10 ) / D 50 , and D 10 , D 90 and D 50 are measured by laser diffraction as described in this specification; and
[0149] · wherein the magnesium compound is magnesium alkoxide, preferably the magnesium alkoxide is magnesium ethoxide Mg(OC2H5)2; and
[0150] · wherein the organo-oxygen-containing titanium compound is represented by the general formula [TiO x (OR) 4-2x n , wherein R represents an organic group, x is 0 - 1, and n is 1 - 6, preferably wherein the organo-oxygen-containing titanium compound is selected from alkoxides, phenoxides, oxoalkoxides, condensed alkoxides, carboxylates and / or enolates, preferably the organo-oxygen-containing titanium compound is an alkoxide.
[0151] Preferably, a catalyst system for producing polyethylene is obtained or can be obtained by a method comprising the following steps:
[0152] a) providing a hydrocarbon solution comprising:
[0153] i) a magnesium-containing compound, wherein the magnesium-containing compound is magnesium ethoxide Mg(OC2H5)2; and
[0154] ii) an organo-oxygen-containing titanium compound I) a), wherein the organo-oxygen-containing titanium compound I) a) is Ti(On-C4H9)4;
[0155] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0156] b) providing an organoaluminum halide I) b) of the formula AlR n X 3-n , wherein R is a hydrocarbon structural moiety containing 1 - 10 carbon atoms, 'X' is a halogen, and 0 < n < 3, wherein the organoaluminum halide I) b) is ethylaluminum dichloride;
[0157] c) introducing a hydrocarbon solution and an organoaluminum halide into the reactor vessel simultaneously; and
[0158] d) obtaining a catalyst system comprising the reaction product of the hydrocarbon solution and ethylaluminum dichloride;
[0159] · wherein the molar ratio of ethylaluminum dichloride to Ti(On-C4H9)4 is 1 - 12; and
[0160] · wherein the average particle size distribution (PSD) of the catalyst particles contained in the catalyst system is 0.8 - 1.6, and wherein PSD is defined as PSD = (D 90 - D 10 ) / D 50 , and D 10 , D 90 and D 50 are measured by laser diffraction as described in this specification.
[0161] Aluminum compounds of the formula AlR3 act as cocatalysts, for example. R3 may be a hydrocarbyl group, preferably an alkyl group having 1 - 20 carbon atoms, preferably 1 - 10 carbon atoms.
[0162] Aluminum compounds of the formula AlR3 may be selected, for example, from triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, and trioctylaluminum. For example, the aluminum compound of the formula AlR3 may be triethylaluminum or triisobutylaluminum.
[0163] Preferably, the catalyst system comprises:
[0164] I) the reaction product obtained by the reaction of the following components:
[0165] a) a hydrocarbon solution comprising:
[0166] i) a magnesium-containing compound selected from organo-oxygenated magnesium compounds, which is magnesium ethoxide (Mg(OC2H5)2); and
[0167] ii) an organo-oxygenated titanium compound of Ti(On-C4H9)4,
[0168] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0169] and
[0170] b) the organoaluminum halide is ethylaluminum dichloride;
[0171] wherein the molar ratio of the organoaluminum halide I) b) supplied in the preparation of I) to the titanium supplied in I) a) is 1 - 12; and
[0172] wherein the average particle size distribution of the catalyst particles is 0.8 - 1.6.
[0173] The catalyst system can be prepared by a method comprising the following steps:
[0174] a) Providing a hydrocarbon solution comprising:
[0175] i) a magnesium-containing compound selected from organo-oxygenated magnesium compounds; and / or halogen-containing magnesium compounds; and
[0176] ii) an organo-oxygenated titanium compound I) a);
[0177] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0178] b) Providing an organoaluminum halide of formula AlR n X 3-n I) b), wherein R is a hydrocarbon moiety containing 1-10 carbon atoms, X is a halogen, and 0 < n < 3;
[0179] c) Simultaneously introducing the hydrocarbon solution and the organoaluminum halide into a reactor vessel; and
[0180] d) Obtaining a catalyst system comprising the reaction product (I) of the reaction of the hydrocarbon solution and the organoaluminum halide.
[0181] Specifically, the catalyst system is prepared by the following steps:
[0182] 1) Providing solutions a) and b)
[0183] Solution a) is a hydrocarbon solution comprising:
[0184] i) a magnesium-containing compound selected from organo-oxygenated magnesium compounds and / or halogen-containing magnesium compounds; and
[0185] ii) an organo-oxygenated titanium compound;
[0186] wherein the molar ratio of magnesium to titanium is less than 3:1;
[0187] Solution b) is a hydrocarbon solution comprising an organoaluminum halide of formula AlR n X 3-n wherein R is a hydrocarbon moiety containing 1-10 carbon atoms, X is a halogen, and 0 < n < 3.
[0188] 2) Simultaneously metering solutions a) and b) into a receiving means such as a reactor so that the molar ratio of the organoaluminum halide of b) supplied to the titanium of a) supplied is within a selected range of 1-12 during metering. For example, the selected molar ratio of the organoaluminum halide of b) supplied to the titanium of a) supplied can be 6. This means that the molar ratio remains constant during the metering of solutions a) and b) so that the molar ratio of the organoaluminum halide of b) supplied to the titanium of a) supplied in the receiving means is 6 at any time.
[0189] 3) Remove unreacted reagents such as soluble Ti and Al species from the catalyst slurry. The soluble contaminants can be removed by filtering or decanting the catalyst slurry.
[0190] For decanting of the catalyst, it is desirable that the catalyst exhibits good sedimentation behavior. Slow sedimentation behavior will increase the time for the decanting step, thus increasing the time for preparing a batch of catalyst. Therefore, it is clearly desirable to reduce the sedimentation time during the catalyst production process. Compared with conventional precipitation methods, the catalyst systems according to the present invention exhibit greatly improved sedimentation behavior.
[0191] Polyethylene, especially high - density polyethylene (HDPE), constitutes a class of materials with a balanced set of material properties, which are particularly desirable for a range of applications, especially for pipes and tubes produced by an extrusion process. For example, high - density polyethylene can have a unimodal or multimodal molecular weight distribution. Such a unimodal or multimodal molecular weight distribution results in a specific balance of material properties.
[0192] The multimodal molecular weight distribution can be achieved by using, for example, two or more cascaded polymerization reactors in a process for producing multimodal HDPE, which process is further referred to as a multi - stage polymerization process. Such multi - stage polymerization processes are described, for example, in "PE 100 Pipe Systems", Bromstrup (ed), Vulkan Verlag, 2004, pages 16 - 20.
[0193] The method for producing polyethylene according to the present invention includes the step of polymerizing ethylene in the presence of a catalyst system according to the present invention.
[0194] Preferably, in one aspect of the present invention, the present invention relates to a method for producing polyethylene, which includes the step of polymerizing ethylene in the presence of a catalyst system according to the present invention and in the presence of a cocatalyst of the formula AlR3, wherein R3 is a hydrocarbyl group, preferably an alkyl group having 1 - 20 carbon atoms, preferably 1 - 10 carbon atoms.
[0195] The polymerization process for producing polyethylene can, for example, include a single polymerization stage. Optionally, the method for producing polyethylene can, for example, include multiple polymerization stages, wherein the method includes at least one slurry polymerization process. The method for producing polyethylene that includes multiple polymerization stages is also referred to as a multi - stage polymerization process.
[0196] The method for producing polyethylene is preferably a multi - stage polymerization method including at least two stages.
[0197] Each individual stage of the multi-stage polymerization process may include a separate polymerization reactor, which are cascaded together to form a multi-stage polymerization process. The operating conditions of each polymerization reactor may be different or the same as those in other polymerization reactors that form the cascade of the multi-stage polymerization process.
[0198] The method for producing polyethylene may be, for example, a slurry polymerization process at low temperature and low pressure. The slurry used in the slurry polymerization process is defined as such a liquid system that contains a diluent as the liquid phase, feed monomers, a catalyst system, and polymer particles formed during the polymerization process.
[0199] As the diluent, a hydrocarbon is used that is not reactive under the conditions occurring during the polymerization process and is in the liquid phase under the conditions occurring during the polymerization process. The diluent may be, for example, hexane. Low-pressure polymerization is defined as polymerization at an ethylene partial pressure of, for example, 0.3 MPa - 5.0 MPa, optionally for example 0.5 MPa - 3.0 MPa, optionally for example 0.5 - 2.0 MPa. Low-temperature polymerization is defined as polymerization at a temperature of, for example, 70 °C - 90 °C.
[0200] The method for producing polyethylene may include at least one stage including a slurry process.
[0201] The method for producing polyethylene may be a multi-stage polymerization process, in which component I) of the catalyst system is introduced in the first stage of the multi-stage polymerization process.
[0202] The catalyst system according to the present invention is sensitive enough to hydrogen for use in a multi-stage polymerization process for producing multi-peak HDPE. In addition, the catalyst system according to the present invention is capable of producing a low molecular weight polymer fraction according to the desired molecular weight distribution characteristics and is also capable of producing a high molecular weight copolymer fraction.
[0203] The method for producing polyethylene using the catalyst system according to the present invention may produce polyethylene with a density ≥ 935 kg / m 3 and ≤ 975 kg / m 3 This density is measured according to ISO 1183-1 (2012), Method A.
[0204] Preferably, the method for producing polyethylene using the catalyst system according to the present invention is a multi-stage method that produces polyethylene as multi-peak polyethylene.
[0205] The weight fraction of polyethylene produced in the first stage of a multi-stage slurry polymerization process can be, for example, greater than 20.0 wt%, optionally greater than 30.0 wt%, optionally greater than 40.0 wt%, compared to the total weight of the polymer produced. The weight fraction of polyethylene produced in the first stage of a multi-stage slurry polymerization process can be, for example, less than 80.0 wt%, optionally less than 70.0 wt%, optionally less than 60 wt%, compared to the total weight of the polymer produced.
[0206] The weight fraction of polyethylene produced in the first stage of a multi-stage slurry polymerization process can be, for example, 40.0 wt% - 60.0 wt% of the total product, or 47 wt% - 58 wt%.
[0207] The polymerization can be carried out, for example, in the presence of one or more anti-fouling agents. For example, up to 500 ppm by weight of the anti-fouling agent can be used, relative to the total amount of the reactor contents.
[0208] The polymerization can be carried out in the presence of one or more antistatic agents. For example, up to 500 ppm of the one or more antistatic agents are used, relative to the total amount of the reactor contents.
[0209] The polyethylene according to the present invention can be unimodal or multimodal polyethylene. In the context of the present invention, unimodal polyethylene is defined as polyethylene having a unimodal molecular weight distribution. In the context of the present invention, multimodal polyethylene is defined as polyethylene having a multimodal molecular weight distribution. The molecular weight distribution is defined as the relationship between the molecular weight of the polymer molecules present in a polymer sample and the number of molecules having that molecular weight in the polymer sample. The multimodal molecular weight distribution reflects the combination of the molecular weight distributions of the polyethylene prepared in each stage of the multi-stage polymerization process.
[0210] The molecular weight distribution of the polyethylene according to the present invention can be determined by size exclusion chromatography, as described, for example, in "Handbook of Polyethylene, structure, properties and applications", A. Peacock, Dekker, New York, 2000, pages 242 - 244.
[0211] The production of polyethylene in a slurry polymerization process is generally carried out in the presence of a catalyst system. Such a catalyst system can, for example, comprise a catalyst, a cocatalyst and an electron donor.
[0212] In the context of the present invention, polyethylene is understood to be the polymer product obtained as the output of the polymerization process.
[0213] Polyethylene is described in "Olefin Polymers, Introduction", Y. Kissin, in: Kirk - Othmer Encyclopedia of Chemical Technology, Wiley, 2005 (DOI: 10.1002 / 0471238961.0914201811091919.a01.pub2).
[0214] In the process for producing polyethylene, the process and the catalyst must form a well - balanced system in order to obtain a product with the desired properties while allowing for an efficient operation of the process.
[0215] The polyethylene obtained or obtainable by the catalyst system according to the invention or by the process according to the invention comprises polyethylene powder particles having an average particle size distribution of 0.70 - 1.40.
[0216] The polyethylene obtained or obtainable by the process according to the invention comprises polyethylene powder particles having an average particle size distribution of 0.70 - 1.40.
[0217] The polyethylene obtained or obtainable by the catalyst system according to the invention or by the process according to the invention comprises polyethylene powder particles having a dry flowability of 15 - 36 s.
[0218] The polyethylene obtained or obtainable by the process according to the invention comprises polyethylene powder particles having a dry flowability of 15 - 36 s.
[0219] The polyethylene obtained or obtainable by the catalyst system according to the invention or by the process according to the invention comprises polyethylene powder particles having an average particle size distribution of 0.70 - 1.40 and a dry flowability of 15 - 36 s.
[0220] The polyethylene obtained or obtainable by the process according to the invention comprises polyethylene powder particles having an average particle size distribution of 0.70 - 1.40 and a dry flowability of 15 - 36 s.
[0221] The polyethylene according to the invention can be, for example, high - density polyethylene, further referred to as HDPE. The polyethylene can be, for example, a polyethylene having a density ≥ 935 kg / m 3 , optionally for example ≥ 940 kg / m 3 . The polyethylene can be, for example, a polyethylene having a density ≤ 975 kg / m 3 , optionally for example ≤ 970 kg / m 3 , optionally for example ≤ 965 kg / m 3 .
[0222] The polyethylene can be, for example, a polyethylene with a density ≥ 935 kg / m 3 and ≤ 975 kg / m 3 , optionally, for example, ≥ 940 kg / m 3 and ≤ 970 kg / m 3 , optionally, for example, ≥ 940 kg / m 3 and ≤ 965 kg / m 3 .
[0223] The polyethylene according to the present invention can be, for example, a multimodal HDPE.
[0224] The multimodal HDPE can be used, for example, to process objects by blow molding, extrusion or injection molding. The multimodal HDPE can be used, for example, to produce films, pipes, tubes and pipe fittings. Examples of multimodal HDPE pipes are pipes for drinking water, sewage, irrigation, natural gas transportation and cable ducts.
[0225] The multimodal HDPE is particularly suitable for processing into pipes and tubes by extrusion. In the context of the present invention, extrusion is defined as a method for shaping a thermoplastic material such as polyethylene, which includes the steps of: providing a thermoplastic material in a moldable state to a die orifice, extruding the thermoplastic material through the die orifice, and cooling the extruded material to a temperature below its softening temperature.
[0226] In the context of the present invention, a thermoplastic material is defined as a material that obtains a moldable state when heated to a temperature above the softening temperature and returns to a solid state when cooled to a temperature below the softening temperature.
[0227] In the context of the present invention, the moldable state is defined as a state in which the material can be formed into a desired shape while maintaining the desired shape when leaving the mold for forming the desired shape. In extrusion, the die orifice serves as the mold.
[0228] An important material parameter of polyethylene is the melt mass-flow rate measured at a temperature of 190 °C and a load of 5.0 kg according to ISO 1133-1 (2011), further referred to as MFR(5).
[0229] The MFR(5) of the multimodal polyethylene can be, for example, ≤ 100 g / 10 min, optionally ≤ 50.0 g / 10 min, optionally ≤ 25.0 g / 10 min, optionally ≤ 10.0 g / 10 min, optionally ≤ 5.00 g / 10 min, optionally ≤ 4.00 g / 10 min, optionally ≤ 3.00 g / 10 min, optionally ≤ 2.00 g / 10 min, optionally ≤ 1.00 g / 10 min.
[0230] The MFR(5) of the multimodal polyethylene can be, for example, ≥ 0.01 g / 10 min, optionally ≥ 0.05 g / 10 min, optionally ≥ 0.10 g / 10 min, optionally ≥ 0.15 g / 10 min. For example, the MFR(5) of the multimodal polyethylene according to the invention can be, for example, ≥ 0.05 g / 10 min and ≤ 10.0 g / 10 min, optionally for example ≥ 0.10 g / 10 min and ≤ 5.00 g / 10 min, optionally for example ≥ 0.15 g / 10 min and ≤ 2.00 g / 10 min.
[0231] Another important material parameter of the polyethylene is the melt mass flow rate determined at a temperature of 190 °C and a load of 21.6 kg in accordance with ISO 1133-1 (2011), further referred to as MFR(21.6).
[0232] The MFR(21.6) of the multimodal polyethylene according to the invention can be, for example, ≤ 500 g / 10 min, optionally ≤ 200 g / 10 min, optionally ≤ 100 g / 10 min, optionally ≤ 50.0 g / 10 min, optionally ≤ 20.0 g / 10 min.
[0233] The MFR(21.6) of the multimodal polyethylene according to the invention can be, for example, ≥ 0.50 g / 10 min, optionally ≥ 1.00 g / 10 min, optionally ≥ 2.00 g / 10 min, optionally ≥ 5.00 g / 10 min, optionally ≥ 10.0 g / 10 min. For example, the MFR(21.6) of the multimodal polyethylene according to the invention can be, for example, ≥ 0.50 g / 10 min and ≤ 200 g / 10 min, optionally for example ≥ 1.00 g / 10 min and ≤ 100 g / 10 min, optionally for example ≥ 1.00 g / 10 min and ≤ 50.0 g / 10 min.
[0234] The present invention will now be illustrated by the following non-limiting examples. Examples
[0235] Measurement methods
[0236] - The melt index MFR 21.6 or melt flow index (MFI) is measured at 190 °C under a load of 21.6 kg according to method ISO 1133.
[0237] - The density of the polymer is measured according to ISO 1183
[0238] - The bulk density is measured according to DINISO 60:2000-01
[0239] - The pourability of the plastic material is carried out according to ASTM D 1895-96
[0240] - The catalyst particle size is measured using laser diffraction. This is carried out using a Mastersizer 3000 instrument equipped with an improved Hydro MV unit for automatic wet dispersion of the sample under an inert atmosphere. The catalyst particle size is calculated using the Mie theory, with an absorption coefficient = 1, a refractive index of the catalyst of 1.596, and a refractive index of the dispersant = 1.39.
[0241] - The polymer particle size is measured using laser diffraction. This is carried out using a Mastersizer 3000 instrument equipped with an AeroS unit for dry powder dispersion of the sample. The catalyst particle size is calculated using the Fraunhofer theory.
[0242] - The particle size distribution (PSD) is calculated according to the following formula:
[0243] PSD = (D 90 - D 10 ) / D 50 , and D 90 is the percentile value representing the size below which 90% of all particles are found. D 10 is the percentile value representing the size below which 10% of all particles are found. D 50 is the percentile value representing the size below which 50% of all particles are found. D 50 is also known as the median particle size or median grain size. These values can be directly determined from the cumulative particle size distribution.
[0244] - Image analysis is carried out on a Malvern Morphology G3SE with a Nikon CFI brightfield / darkfield inspection microscope (Eclips L200ND) and a Baumer 5M pixel CCD digital color camera. An aliquot of polyethylene powder of 19 - 38 mm 3 is dried and dispersed in air on a glass object with the following settings using a solid dispersion unit (SDU): an air pulse of 1 bar for 20 milliseconds and a sedimentation time of 600 seconds. A magnification of 5× is used. To achieve precise focusing covering the entire body of small three - dimensional particles and large three - dimensional particles, up to 5 images of the particles are taken at different foci and then combined to provide a single composite image.
[0245] - Catalyst preparation
[0246] A) Preparation of Precursor (A) (Preparation of Solution I)
[0247] Under a nitrogen atmosphere, 132.5 g of granular Mg(OC2H5)2 and 199 ml of Ti(On-C4H9)4 (both at a temperature of 25 °C) were introduced into a 2 L round-bottom flask equipped with a reflux condenser and a stirrer. Under gentle stirring, the mixture was heated to 180 °C and then stirred for 90 minutes. A clear liquid was obtained. The contents of the round-bottom flask were cooled to 120 °C and then diluted with 1318 g of hexane. The contents of the round-bottom flask were cooled to 67 °C. The temperature was maintained at 67 °C for 120 minutes and then cooled to 25 °C. The resulting solution was stored under a nitrogen atmosphere. A solution with a Ti concentration of 1.82 wt% was obtained.
[0248] B1) Preparation of Invention Catalyst 1, Invention Catalyst 1 (prepared by simultaneously adding Solution I and Solution II to a glass reaction vessel)
[0249] All equipment and glassware were dried and kept under inert conditions during the synthesis.
[0250] 305 mL of hexane was introduced into a 1.0 L glass reactor equipped with baffles, a reflux condenser, and a stirrer.
[0251] Solution I (hydrocarbon solution)
[0252] 157 mL of precursor A was added to a Schlenk flask using a graduated pipette.
[0253] Solution II (organoaluminum halide)
[0254] In a separate Schlenk flask, 75 mL of a 50 wt% solution of ethylaluminum dichloride (EADC) in hexane was added to 82 mL of hexane.
[0255] A peristaltic pump was installed to connect the two Schlenk flasks to the 1.0 L glass reactor.
[0256] Then, using the following peristaltic pump and reactor settings, the contents of the Schlenk flasks (Solution I and Solution II) were simultaneously transferred dropwise into the reactor. Solutions I and II were gradually introduced into the glass reactor simultaneously over 18 minutes using the peristaltic pump. The simultaneous addition of Solutions I and II is a key aspect of this procedure.
[0257] Reactor temperature = 25 °C
[0258] Reactor stirrer speed = 1400 RPM
[0259] Peristaltic pump speed = 18 RPM (calibrated to transfer 157 mL of Solution II in 18 minutes)
[0260] Peristaltic pump speed = 18 RPM (calibrated to transfer 157 mL of Solution I in 18 minutes)
[0261] After adding the two solutions, the temperature of the reactor was set to 71 °C and the mixture was refluxed for 2 hours. The contents were transferred to a P4 filter and washed with 2 L of hexane. The washed catalyst was transferred to a 500 mL round-bottom flask and stored in a nitrogen box.
[0262] B2) Preparation of Invention Catalyst 2, Invention Catalyst 2 (prepared by simultaneously adding Solution I and Solution II to a glass reaction vessel)
[0263] All equipment and glassware were dried and kept under inert conditions during the synthesis.
[0264] 371 mL of hexane was introduced into a 1.0 L glass reactor equipped with a baffle, a reflux condenser, and a stirrer.
[0265] Solution I (hydrocarbon solution)
[0266] 124 mL of precursor A was added to a Schlenk flask using a graduated pipette.
[0267] Solution II (organoaluminum halide)
[0268] In a separate Schlenk flask, 59 mL of a 50 wt% solution of ethylaluminum dichloride (EADC) in hexane was added to 65 mL of hexane.
[0269] A peristaltic pump was installed to connect the two Schlenk flasks. Then, using the following peristaltic pump and reactor settings, the contents of the Schlenk flasks were simultaneously transferred dropwise to the reactor. Solutions I and II were gradually introduced into the glass reactor simultaneously using the peristaltic pump over 19 minutes. The simultaneous addition of Solutions I and II is a key aspect of this procedure.
[0270] Reactor temperature = 25 °C
[0271] Reactor stirrer speed = 1400 RPM
[0272] Peristaltic pump speed = 16 RPM (calibrated to transfer 124 mL of Solution II in 19 minutes)
[0273] Peristaltic pump speed = 16 RPM (calibrated to transfer 124 mL of Solution I in 19 minutes)
[0274] After adding the two solutions, the temperature of the reactor was set to 71 °C and the mixture was refluxed for 2 hours. The contents were transferred to a P4 filter and washed with 2 L of hexane. The washed catalyst was transferred to a 500 mL round-bottom flask and stored in a nitrogen box.
[0275] B3) Preparation of Invention Catalyst 3, Invention Catalyst 3 (prepared by simultaneously adding Solution I and Solution II to a glass reaction vessel)
[0276] Dry all apparatus and glassware and keep under inert conditions during synthesis.
[0277] Introduce 380 mL of hexane into a 1.0 L glass reactor equipped with a baffle, reflux condenser, and stirrer.
[0278] Solution I (hydrocarbon solution)
[0279] Add 124 mL of precursor A to a Schlenk flask using a graduated pipette.
[0280] Solution II (organoaluminum halide)
[0281] In a separate Schlenk flask, add a 50 wt% solution of 42 mL of ethylaluminum dichloride (EADC) in hexane to 23 mL of hexane.
[0282] Install a peristaltic pump to connect the two Schlenk flasks. Then use the following peristaltic pump and reactor settings to transfer the contents of the Schlenk flasks dropwise into the reactor simultaneously.
[0283] Introduce Solutions I and II gradually and simultaneously into the glass reactor using the peristaltic pump over 18 minutes. The simultaneous addition of Solutions I and II is a key aspect of this procedure.
[0284] Reactor temperature = 25 °C
[0285] Reactor stirrer speed = 1400 RPM
[0286] Peristaltic pump speed = 31 RPM (calibrated to transfer 124 mL of Solution II in 18 minutes)
[0287] Peristaltic pump speed = 14 RPM (calibrated to transfer 65 mL of Solution I in 18 minutes)
[0288] After adding the two solutions, set the temperature of the reactor to 71 °C and reflux the mixture for 2 hours. Transfer the contents to a P4 filter and wash with 2 L of hexane. Transfer the washed catalyst to a 500 mL round-bottom flask and store in a nitrogen box.
[0289] C1) Preparation of Comparative Catalyst 1, Comparative Catalyst 1 (prepared by sequentially adding Solution II and then Solution I instead of simultaneously)
[0290] Dry all apparatus and glassware and keep under inert conditions during synthesis.
[0291] Introduce 300 mL of hexane into a 1.0 L glass reactor equipped with a baffle, reflux condenser, and stirrer.
[0292] Solution I
[0293] 157 mL of precursor A was added to the glass reactor using a graduated pipette.
[0294] Solution II
[0295] In a separate Schlenk flask, 59 mL of a 50 wt% solution of ethylaluminum dichloride (EADC) in hexane was added to 42 mL of hexane. Solution II was gradually introduced into the glass reactor over 15 minutes using a peristaltic pump.
[0296] A peristaltic pump was installed to connect the Schlenk flask containing Solution II to the reactor containing Solution I with precursor A.
[0297] The contents of the Schlenk flask were then transferred dropwise to the reactor using the following peristaltic pump and reactor settings. For the purpose of the comparative example, Solution II was added sequentially to the glass reactor already containing Solution I.
[0298] Reactor temperature = 25 °C
[0299] Reactor stirrer speed = 1400 RPM
[0300] Peristaltic pump speed = 18 RPM (calibrated to transfer 117 mL of EADC in 15 minutes)
[0301] After adding the EADC solution, the tubing of the peristaltic pump was rinsed with 50 mL of hexane. The temperature of the reactor was set to 71 °C and the mixture was refluxed for 2 hours. The contents were transferred to a P4 filter and washed with 2 L of hexane. The washed catalyst was transferred to a 500 mL round-bottom flask and stored in a nitrogen box.
[0302] Table 1: Reactor conditions, elemental composition, and particle size of the catalyst
[0303]
[0304] The catalyst particles of Inventive Catalysts 1-3 have a significantly lower particle size span compared to Comparative Catalyst 1 of the comparative example.
[0305] The catalyst system according to the present invention (Inventive Catalysts 1-3) exhibits a reduced settling time, which is at least 40% shorter compared to the comparative example (Comparative Catalyst 1).
[0306] It seems that the method of adding Solution I and Solution II to the glass reactor has a certain effect on the average particle size distribution of the catalyst particles.
[0307] - Polymerization Experiment
[0308] D) Homopolymerization of Ethylene
[0309] Add 5 L of anhydrous hexane to a reactor with an internal volume of 10 L and equipped with a stirrer. Then, add a hexane solution of 0.8 mol / L triisobutylaluminum (TiBAl) to the reactor. Heat the contents to the desired polymerization temperature while stirring at 750 RPM. Add ethylene and hydrogen at a certain partial pressure ratio (pC2 and pH2 respectively) to achieve the desired pressure in the reactor. Then, add an aliquot of a catalyst suspension containing a predetermined amount of solid catalyst of one of the above catalysts as shown in the table above (Table 1) to the reactor to start the polymerization. Keep the total pressure of the reactor constant by metering ethylene. The ratio of hydrogen to ethylene (H2 / C2) in the reactor headspace is continuously monitored by gas chromatography and kept constant by metering hydrogen as needed. After a polymerization time of 120 minutes, reduce the pressure of the reactor to ambient conditions and purge the reactor with nitrogen. Cool the reactor temperature to 35 °C, then filter the slurry to collect the wet polymer fluff. The polymer is then rinsed with 10 L of hexane, collected and vacuum dried in an oven at 40 °C for 18 hours. Weigh the dried polymer and analyze the density and melt flow index (MFR 190 / 21.6 ).
[0310] The setup used for the polymerization experiment can be found in Table 2.
[0311] Table 2: Ethylene Homopolymerization Reactor Setup
[0312]
[0313] Table 3: PE Powder Morphology
[0314]
[0315] The PE homopolymer powder samples made with inventive catalysts 1 - 3 have a significantly lower particle size span compared to the PE powder sample made with the comparative catalyst 1 of the comparative example. For inventive catalysts 1 - 3, the fraction of very fine particles (<105 μm) is lower, as indicated by D 10 . Also, the dry flowability of catalysts 1 - 3 is significantly faster. This means that the PE powder will flow more easily, thus for example improving the metering of polyethylene powder into the extruder.
[0316] Figure 1 The laser diffraction PSD curves of the homopolymerization of PE powder from Examples 1 - 4 are shown.
[0317] Figure 2Shows the image analysis of Example 2 and Comparative Example 4.
[0318] Figure 3 Shows a representative SEM image of the PE powder from Example 2. It can be seen that for the catalyst 2 of Example 2, the polymer powder does not show a particle size of <100 μm.
[0319] Figure 4 Shows a representative SEM image of the PE powder from Comparative Example 4. It is evident from the image that the polymer powder of Comparative Example 4 shows a large number of particles of <100 μm.
[0320] E) Copolymerization of Ethylene
[0321] The procedure for these experiments is similar to the above-mentioned ethylene homopolymerization procedure, except that before the start of polymerization, after the quantitative feeding of hydrogen (before the quantitative feeding of ethylene), 1-butene is directly metered into the reactor. The molar ratio of 1-butene to ethylene (C4 / C2) in the reactor headspace is continuously measured by gas chromatography, and 1-butene is fed as needed to maintain the ratio at the desired value. The settings used for the polymerization experiments can be found in Table 4.
[0322] Table 4: Ethylene copolymerization reactor settings
[0323]
[0324] Table 5: PE powder morphology
[0325]
[0326] * The dry flowability of the powder of the sample is achieved only by tapping on the dry flow funnel
[0327] The PE powder sample produced with the inventive catalyst 2 has a much lower particle size span compared to the PE powder sample produced with the comparative catalyst 1 of the comparative example. For the inventive catalyst 2, the fraction of very fine particles (<105 μm) is lower, as indicated by D 10 >105 μm. Similarly, compared to Comparative Example 8, the dry flowability of catalyst 2 is significantly faster, where the powder flow can be initiated only by tapping on the dry flow funnel.
[0328] Figure 5 Is the laser diffraction PSD curve of Example 7 (catalyst 2 of the present invention).
[0329] Figure 6 Shows the SEM image of the PE copolymer of catalyst 2 of Example 7.
[0330] Figure 7 Shows the SEM image of the PE copolymer of the comparative catalyst 1 of Example 8
[0331] Figure 8 Shows the PSD curves of the light scattering image analysis of the PE polymers of Example 7 and Comparative Example 8.
[0332] It is evident from the results that the average particle size distribution of the catalyst particles affects the powder morphology of the polymer powder and thus affects its fluidity. It has been surprisingly found that the method of adding Solution I (hydrocarbon solution) and Solution II (organoaluminum halide) affects the catalyst particle morphology, which in turn affects the average particle size distribution of the polymer powder.
Claims
1. A catalyst system for producing polyethylene, the catalyst system comprising: I) A reaction product obtained by reacting the following components, preferably in a reactor vessel: a) A hydrocarbon solution comprising: i) A magnesium compound selected from organo-oxygen-containing magnesium compounds and / or halogen-containing magnesium compounds; and ii) An organo-oxygen-containing titanium compound, wherein the molar ratio of magnesium to titanium is less than 3:1; and b) Organoaluminum halide of the formula AlR n X 3-n , where R is a hydrocarbon moiety containing 1 to 10 carbon atoms, X is a halogen, and 0 < n < 3; wherein the molar ratio of organoaluminum halide I)b) supplied in the preparation of I) to titanium supplied in I)a) is 1 - 12; and wherein the average particle size distribution (PSD) of the catalyst particles is 0.8 - 1.6, and wherein the PSD is defined as PSD = (D 90 - D 10 ) / D 50 , and D 10 , D 90 and D 50 are measured by laser diffraction as described in the specification, preferably wherein the hydrocarbon solution and the organoaluminum halide are simultaneously supplied to the reactor vessel.
2. The catalyst system according to claim 1, wherein the average particle size distribution of the catalyst particles is 0.8 - 1.
5.
3. The catalyst system according to any one of the preceding claims, wherein the median particle size D 50 of the catalyst particles is 3.5 - 12.50 μm, preferably 4.50 - 10 μm, more preferably 4.50 - 8 μm, which is measured by laser diffraction.
4. The catalyst system according to any one of the preceding claims, wherein the molar ratio of organoaluminum halide I)b) supplied in the preparation of I) to titanium supplied in I)a) is 4 - 12, preferably 5 - 10, more preferably 5 - 9, most preferably 6 - 9.
5. The catalyst system according to any one of the preceding claims, wherein the magnesium compound is magnesium alkoxide, preferably the magnesium alkoxide is magnesium ethoxide Mg(OC2H5)2.
6. The catalyst system according to any one of the preceding claims, wherein the organo-oxygenated titanium compound is represented by the general formula [TiO x (OR) 4-2x n wherein R represents an organic group, x is 0 - 1, and n is 1 - 6. 7. The catalyst system according to claim 6, wherein the organo-oxygen-containing titanium compound is selected from alkoxides, phenoxides, oxoalkoxides, condensed alkoxides, carboxylates and / or enolates.
8. The catalyst system according to claims 6-7, wherein the organo-oxygen-containing titanium compound is titanium alkoxide, and the titanium alkoxide is preferably selected from Ti(OC4H9)4, Ti(OC2H5)4, Ti(OC3H7)4 and / or Ti(OC8H 17 )4, and most preferably Ti(OC4H9)4.
9. A catalyst system according to any one of the preceding claims, wherein the organoaluminium halide has the formula AlR n X 3-n , where X is chlorine.
10. The catalyst system according to claim 9, wherein the organoaluminum halide is ethylaluminum dichloride (EADC).
11. A method for producing polyethylene, which comprises the step of polymerizing ethylene in the presence of a catalyst system according to any one of the preceding claims and in the presence of a cocatalyst of the formula AlR3, wherein R3 is a hydrocarbon group, preferably an alkyl group having 1 - 20 carbon atoms, preferably 1 - 10 carbon atoms.
12. The method for producing polyethylene according to claim 11, wherein the method is a multi-stage polymerization method comprising at least two stages.
13. The method for producing polyethylene according to any one of claims 11 - 12, wherein at least one stage of the method comprises a slurry process.
14. The method according to any one of claims 11 - 13, wherein the component I) of the catalyst system is introduced in the first stage of the multi-stage polymerization method. Polyethylene obtained by the catalyst system according to claims 1 - 10 or by the method according to claims 11 - 14, wherein the average particle size distribution of the polyethylene powder particles is 0.70 - 1.40; and / or the dry flowability is 15 - 36 s.